Nitrogen-doped and graphitized optimized coal-based hard carbon material as well as preparation method and application thereof
By simplifying the process and reducing costs, coal-based hard carbon materials optimized by nitrogen doping and graphitization were prepared, solving the problems of poor conductivity and disordered structure in sodium ion batteries, and achieving high-efficiency and low-cost negative electrode materials for sodium ion batteries.
Patent Information
- Application Number
- CN202411934101.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-11
AI Technical Summary
The existing hard carbon materials have poor conductivity, disordered structure, complex preparation processes and high cost in sodium ion batteries, which limit their development in large-scale energy storage applications.
The coal-based hard carbon materials optimized for nitrogen doping and graphitization are prepared through fluoride salt removal, mixed carbon sources, and high-temperature sintering. Urea is used as a nitrogen source and catalyst to simplify the process and reduce costs.
The prepared hard carbon material has a mesoporous structure, nitrogen doping and uniform graphite domains, ensuring fast kinetics and electron transfer, and achieving a sodium ion battery negative electrode material with high Coulomb efficiency, large reversible capacity, excellent rate performance and low cost.
Smart Images

Figure CN119797316A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a nitrogen-doped and graphitized optimized coal-based hard carbon material and a preparation method and application thereof. Background Art
[0002] As the proportion of renewable energy utilization increases year by year, due to its intermittent and volatile characteristics, it is urgent to develop large-scale and efficient energy storage devices for voltage regulation and secondary distribution. Lithium-ion batteries are the current mainstream products, but lithium resources are limited in reserves, expensive, and unevenly distributed. Moreover, lithium-ion batteries are composed of highly active electrode materials and organic electrolytes, which are prone to thermal runaway and therefore have low safety. There is an urgent need to seek safer and cheaper energy storage technologies to meet the market's large-scale energy storage needs. Sodium resources are abundant, and sodium-ion batteries are expected to replace lithium-ion batteries and become a solution for large-scale energy storage technology. As an important component of sodium-ion batteries, the battery negative electrode determines the capacity and voltage of the battery. Currently, sodium negative electrode materials can be divided into four categories according to the reaction type: organic, alloy, conversion, and embedding.
[0003] Carbon negative electrode materials represented by hard carbon are one of the main research directions. At present, hard carbon is mainly made by high-temperature carbonization with biomass, high molecular polymers, etc. as raw materials. There are generally problems such as low carbon yield, complex process and high cost, which restrict the further development of the hard carbon industry. It is an important development direction to develop low-cost and high-performance sodium ion electrode materials with high carbon abundance and high reserves of coal in nature as raw materials. However, the intrinsically disordered microstructure of hard carbon made by direct carbonization of coal usually leads to poor conductivity, resulting in low rate capacity. These problems can be solved by rationally designing open nanopores, closed pores surrounded by short-range carbon structures, and hard carbon with high specific surface area through fast reaction kinetics. Unfortunately, the intrinsically disordered microstructure of hard carbon is still retained. The conductivity of hard carbon can be improved by adjusting the degree of graphitization of hard carbon through catalyst-assisted synthesis. This unique hard carbon composed of graphite domains and disordered structures can improve electrochemical performance and charge storage capacity. In addition, doping hard carbon with heteroatoms (such as N, O, and F) can also improve the intrinsic conductivity of hard carbon by introducing active sites and promoting electron transfer, thereby significantly improving the Na ion storage capacity of hard carbon. However, the existing synthetic strategies for preparing graphite domains and doping hard carbon with heteroatoms usually involve multiple steps and harsh reaction conditions. Therefore, in practical applications, an effective and concise synthetic process for preparing graphite domains and doping hard carbon with heteroatoms is urgently needed. Summary of the invention
[0004] The purpose of the present invention is to propose a nitrogen-doped and graphitized coal-based hard carbon material and its preparation method and application to solve the problems mentioned in the background technology; the present invention prepares the hard carbon material through the steps of fluoride salt impurity removal, mixed carbon source, high-temperature sintering and the like, and uses urea as a nitrogen source and catalyst. The prepared hard carbon material has low cost, simple process and optimized graphitization, and has the advantages of mesoporous structure, nitrogen doping and uniform graphite domains, which ensures fast kinetics and electron transfer, thereby obtaining a sodium ion battery with high first charge and discharge coulomb efficiency, large reversible capacity, excellent rate performance and lower cost.
[0005] To solve the above problems, the present invention specifically adopts the following technical solutions:
[0006] A method for preparing a nitrogen-doped and graphitized coal-based hard carbon material comprises the following steps:
[0007] S1. Ball milling and screening: ball milling and screening the raw coal to obtain coal powder with a particle size of less than 74 μm;
[0008] S2, removing ash: mixing coal powder with hydrochloric acid and fluoride salt for 6 to 12 hours, washing with water for 2 to 5 times, and drying to obtain coal powder with ash removed;
[0009] S3, mixing coal powder and nitrogen source: placing the coal powder removed from ash and the nitrogen source together in a ball mill and mixing by ball milling to obtain a solid phase mixture;
[0010] S4. High-temperature sintering: placing the solid phase mixture in a tubular furnace and sintering it at a high temperature under a protective atmosphere to obtain a nitrogen-doped and graphitized optimized coal-based hard carbon material.
[0011] Preferably, the raw coal in S1 is anthracite.
[0012] Preferably, the ratio of the coal powder to hydrochloric acid and fluoride salt in S2 is 1g: (20-80)ml: (0.5-2)g, and more preferably 1g: 50ml: 1g.
[0013] Preferably, the concentration of hydrochloric acid in S2 is 5 mol / L; and the fluoride salt is lithium fluoride.
[0014] Preferably, the nitrogen source in S3 includes one or more of urea, melamine and aniline; and the mass ratio of the coal powder to the nitrogen source is 1:(0.1-1).
[0015] Preferably, the high temperature sintering process in S4 is: heating to 1200-1400° C. at a heating rate of 1-5° C. / min, and keeping the temperature for 1-3 hours; the protective atmosphere is N 2 .
[0016] Preferably, the treatment process of the coal powder in S2 is deashing to remove impurities inside the coal powder and improve its purity.
[0017] The present invention further protects a nitrogen-doped and graphitized optimized coal-based hard carbon material prepared by the above method.
[0018] The present invention further protects the use of the above-mentioned nitrogen-doped and graphitized optimized coal-based hard carbon material in preparing the negative electrode of a sodium ion battery.
[0019] Compared with the prior art, the present invention provides a nitrogen-doped and graphitized optimized coal-based hard carbon material and a preparation method and application thereof, which have the following beneficial effects:
[0020] The preparation method of the nitrogen-doped and graphitized coal-based hard carbon material provided by the present invention has a simpler process and lower overall cost than the prior art. The deashing method of the mixture of coal powder, fluoride salt and hydrochloric acid makes the impurity removal method of the raw coal simpler and lower in cost. The graphitization of the coal-based hard carbon material finally prepared is optimized by urea-catalyzed high-temperature sintering, and has the advantages of mesoporous structure, nitrogen doping and uniform graphite domains, ensuring fast kinetics and electron transfer. The coal-based hard carbon material prepared by this method is used for the negative electrode of a sodium ion battery. At a current density of 30mAg -1 Provides more than 290mA hg -1 The high reversible capacity, greater than 85% first charge-discharge efficiency, strong rate capability and long cycle life indicate that it is a promising SIB anode.
[0021] In summary, the preparation method of the nitrogen-doped and graphitized optimized coal-based hard carbon material for the negative electrode of sodium ion battery proposed in the present invention is simple and easy to operate, has low overall cost, is easy to scale up production, and well meets the conditions for industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 A flow chart of the method for preparing the nitrogen-doped and graphitized optimized coal-based hard carbon material proposed in the present invention;
[0024] Figure 2 TEM images and mapping images of coal-based hard carbon materials prepared in Example 1 and Comparative Example 1;
[0025] Figure 3 XRD patterns of coal-based hard carbon materials prepared in Example 1 and Comparative Example 1;
[0026] Figure 4 Nitrogen adsorption-desorption isotherms and pore size distribution diagrams (inset) of the coal-based hard carbon materials prepared in Example 1 and Comparative Example 1;
[0027] Figure 5 The Raman spectra of the coal-based hard carbon materials prepared in Example 1 and Comparative Example 1;
[0028] Figure 6 The charge and discharge curves of the coal-based sodium ion batteries prepared in Example 1 and Comparative Example 1;
[0029] Figure 7 The scatter plot of rate performance of coal-based sodium ion batteries prepared in Example 1 and Comparative Example 1;
[0030] Figure 8 The scatter plot of the cycle stability performance of the coal-based sodium ion battery prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0031] The technical solution and its effects of the present invention are further described below in conjunction with specific implementation modes / examples. The following implementation modes / examples are only used to illustrate the content of the present invention, and the present invention is not limited to the following implementation modes or examples.
[0032] Embodiment 1:
[0033] (1) The raw coal is ball-milled and sieved to obtain coal powder with a particle size less than 74 μm; the ball mill speed is 100 r / min, and the ball milling time is 24 h.
[0034] (2) Take 5 g of sieved coal powder and 5 g of lithium fluoride, add 150 ml of 5 mol / L hydrochloric acid solution, heat in a 60°C water bath for 12 h, filter, rinse with water until neutral, and dry in a 70°C oven overnight;
[0035] (3) Take 1 g of the treated coal powder and add 0.15 g of urea into a ball mill for mixing; the ball mill speed is 100 r / min and the ball milling time is 6 h.
[0036] (4) The ball-milled solid phase mixture was added into a high-temperature tube furnace, heated to 1300°C at a heating rate of 2°C / min in a nitrogen atmosphere, kept at this temperature for 2 h, cooled to 500°C at a cooling rate of 10°C / min, and then naturally cooled to room temperature to obtain nitrogen-doped and graphitized optimized coal-based hard carbon material for sodium ion battery negative electrode.
[0037] Embodiment 2:
[0038] Based on Example 1, the difference is that step (2) is replaced by: taking 1g of treated coal powder and adding 0.1g of urea into a ball mill for ball milling; the ball mill speed is 100r / min, and the ball milling time is 6h. The other steps and parameters are the same as those in Example 1.
[0039] Embodiment 3:
[0040] Based on Example 1, the difference is that step (2) is replaced by: taking 1g of the treated coal powder and adding 0.5g of urea into a ball mill for ball milling; the ball mill speed is 100r / min, and the ball milling time is 6h. The other steps and parameters are the same as those in Example 1.
[0041] Embodiment 4:
[0042] Based on Example 1, the difference is that step (2) is replaced by: taking 1g of the treated coal powder and 1g of urea, adding them into a ball mill and mixing them; the ball mill speed is 100r / min, and the ball milling time is 6h. The other steps and parameters are the same as those in Example 1.
[0043] Comparative Example 1:
[0044] Based on Example 1, but different in that steps (3) and (4) are replaced by: 1 g of treated coal powder is added to a high-temperature tube furnace, heated to 1300°C at a heating rate of 2°C / min under a N2 atmosphere, kept at that temperature for 2 hours, cooled to 500°C at a cooling rate of 10°C / min, and then naturally cooled to room temperature, to obtain a coal-based hard carbon material for a negative electrode of a sodium ion battery. The other steps and parameters are the same as those in Example 1.
[0045] Battery assembly and testing
[0046] The hard carbon material prepared above was mixed with carbon nanotubes (CNTs) and sodium alginate (SA) in a mass ratio of 8:1:1, and then the slurry was coated on copper foil, dried at 100°C in a vacuum oven for 12 hours, and then cut into electrode sheets with a diameter of 16 mm (the loading amount of each electrode sheet was about 1.5 mg). The sodium sheet was used as the counter electrode, the glass fiber membrane was used as the diaphragm, and 1 mol·L - 1 The NaPF6 diethylene glycol dimethyl ether solution was used as the electrolyte and assembled into a CR2032 button cell in a glove box. A high-precision battery tester (Shenzhen Xinwei) was used to perform constant current charge and discharge tests at a current density of 0.1C (1C = 300mA) and a voltage range of 0.01-3.0V. The test results are shown in Table 1.
[0047] Table 1
[0048]
[0049] It can be seen from Table 1 that nitrogen-doped and graphitized optimized coal-based hard carbon materials can be obtained by urea catalysis and high-temperature sintering. The suitable defects and excellent conductivity of the coal-based hard carbon materials have a certain influence on the first-cycle coulomb efficiency. For example, in Example 1 and Comparative Example 1, the first charge and discharge efficiencies are 88.1% and 79.8%, respectively.
[0050] Comparing the data of Examples 1-4 and Comparative Example 1 in Table 1, the battery performance of Examples 1-4 is improved. The reason is that the anthracite has a structure with more mesopores and a greater degree of graphitization after high-temperature catalysis of urea, so the ion transmission rate is faster and the electronic conductivity is better. At the same time, the addition of a small amount of N also increases the Na + Providing more defect sites, the combined effect of the two exhibits optimal performance at the ratio of Example 1.
[0051] Comparing the data of Examples 1-4 in Table 1, as the amount of urea increases, L a and L c It gradually increases, that is, the unit cell gradually becomes larger and the degree of graphitization becomes larger, among which Example 1 has the best effect.
[0052] Comparing the data of Examples 1-4 in Table 1, as the amount of urea increases, the interlayer spacing d 002 It gradually decreases, among which the coal-based hard carbon material in Example 1 has a suitable interlayer spacing and the best performance.
[0053] Figure 2 The TEM images and Mapping images of the coal-based hard carbon materials prepared in Example 1 and Comparative Example 1. From the TEM image, it can be seen that the hard carbon material prepared by direct one-step carbonization in Comparative Example 1 exhibits a disordered pseudo-graphite structure, while Example 1 after urea catalysis and high-temperature sintering presents the coexistence of graphite domains and disordered carbon domains. From the Mapping image, it can be seen that C, N, and O are evenly distributed in Example 1, indicating that the urea-derived nitrogen has been successfully doped.
[0054] Figure 3 The XRD patterns of the coal-based hard carbon materials prepared in Example 1 and Comparative Example 1 show that they have the structure of hard carbon. Figure 3 It can be seen that compared with the comparative example 1 without urea catalytic treatment, the (002) peak of Example 1 has a slight rightward shift (expressed as d 002 The graphite content of the coal-based hard carbon material prepared in Example 1 is slightly higher, the conductivity is better, and the battery rate performance is more excellent.
[0055] Figure 4 The nitrogen adsorption-desorption isotherms and pore size distribution diagrams (inset) of the coal-based hard carbon materials prepared in Example 1 and Comparative Example 1 are shown in FIG. Figure 4It can be seen that the specific surface areas of Example 1 and Comparative Example 1 are 20.1806 m 2 g -1 and 9.9024m 2 g -1 Coal-based hard carbon materials with higher specific surface area can be obtained through urea catalysis and high-temperature sintering.
[0056] Figure 5 The Raman spectra of the coal-based hard carbon materials prepared in Example 1 and Comparative Example 1 are shown in FIG. Figure 5 It can be seen that with urea catalysis, the disorder degree of Example 1 after high-temperature sintering is reduced from 1.11 to 0.98 compared with Comparative Example 1, which is consistent with the results shown in the TEM image.
[0057] Figure 6 The charge and discharge curves of the coal-based sodium ion battery prepared in Example 1 and Comparative Example 1 are shown in FIG. Figure 6 It can be seen that when the current density of the prepared coal-based hard carbon material is 0.1C, the discharge characteristics of the slope area and the platform area of Example 1 are improved compared with those of Comparative Example 1, the first charging capacity is increased from 230.90 to 291.45 mAh / g, and the first coulombic efficiency is increased to 88.1%.
[0058] Figure 7 The rate performance scatter plot of the coal-based sodium ion battery prepared in Example 1 and Comparative Example 1 (the current densities during the rate performance test were 0.03A / g, 0.05A / g, 0.1A / g, 0.2A / g, 0.5A / g, 1A / g and 0.03A / g, respectively) shows that the capacitance of the battery in Example 1 at a current density of 0.03A / g is 291.45mAh / g, and at a high current density of 1A / g, the capacity is still 222.08mAh / g; the capacitance of the battery in Comparative Example 1 at a current density of 0.03A / g is 230.9mAh / g, and at a high current density of 1A / g, the capacity is only 148.18mAh / g.
[0059] Figure 8 The scatter plot of the cycle stability performance of the coal-based sodium ion battery prepared in Example 1 and Comparative Example 1 is shown in FIG. Figure 8 It can be seen that at 1A g -1 After 500 cycles at a high current density, Example 1 still has 132.7 mAh g -1 The capacity retention rate is about 60%, and the cycle charge and discharge stability is good.
[0060] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and improved concepts of the present invention within the technical scope disclosed by the present invention, and they should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a nitrogen-doped and graphitized coal-based hard carbon material, characterized in that: The following steps are involved: S1. Ball milling and screening: ball milling and screening the raw coal to obtain coal powder with a particle size of less than 74 μm; S2, removing ash: mixing coal powder with hydrochloric acid and fluoride salt for 6 to 12 hours, washing with water for 2 to 5 times, and drying to obtain coal powder with ash removed; S3, mixing coal powder and nitrogen source: placing the coal powder removed from ash and the nitrogen source together in a ball mill and mixing by ball milling to obtain a solid phase mixture; S4. High-temperature sintering: placing the solid phase mixture in a tubular furnace and sintering it at a high temperature under a protective atmosphere to obtain a nitrogen-doped and graphitized optimized coal-based hard carbon material.
2. The method according to claim 1, characterized in that The ratio of coal powder to hydrochloric acid and fluoride salt in S2 is 1g: (20-80)ml: (0.5-2)g.
3. The method according to claim 2, characterized in that The ratio of coal powder to hydrochloric acid and fluoride salt in S2 is 1g:50ml:1g.
4. The method according to claim 1, characterized in that: The concentration of the hydrochloric acid in S2 is 4-6 mol / L.
5. The method according to claim 1, characterized in that The fluoride salt in S2 is lithium fluoride.
6. The method according to claim 1, characterized in that The nitrogen source in S3 includes one or more of urea, melamine and aniline; the mass ratio of the coal powder to the nitrogen source is 1:(0.1-1).
7. The method according to claim 1, characterized in that: The high temperature sintering process described in S4 is: heating to 1200-1400° C. at a heating rate of 1-5° C. / min, and keeping the temperature for 1-3 hours.
8. A nitrogen-doped and graphitized optimized coal-based hard carbon material prepared by the method according to any one of claims 1 to 7.
9. Use of the nitrogen-doped and graphitized optimized coal-based hard carbon material as claimed in claim 8 in preparing a negative electrode for a sodium ion battery.
Citation Information
Patent Citations
Multi-scale regulation and control method for graphitization degree of low-rank coal-based porous carbon
CN114291806A
Anthracite-based nitrogen-doped carbon material as well as preparation method and application thereof
CN116216692A
Nitrogen-doped coal-based hard carbon material, preparation method and application thereof, and secondary battery
CN116443850A
Preparation method and application of coal-based derivative hard carbon material for effectively coordinating sodium storage in platform area and slope area
CN118239470A
Heteroatom doped coal-based hard carbon negative electrode material, preparation method and application thereof, and battery
CN118255344A
Cited By
Hard carbon negative electrode material and preparation method thereof
CN120364677A